Perception and readiness of community pharmacists in delivering palliative care services in Saudi Arabia: a new role in the game - Alshahrani, Sultan M. (Frontiers in Pharmacology, 2025)
BackgroundPalliative care (PC) improves the quality of life for patients with life-limiting illnesses; however, the involvement of community pharmacists in Saudi Arabia remains underexplored. This study evaluates community pharmacists’ perspectives, readiness, and barriers to providing pharmaceutical care services within the Vision 2030 healthcare transformation framework.MethodsA cross-sectional survey was conducted among 267 licensed community pharmacists in the Aseer region of Saudi Arabia using convenience sampling. Participants were recruited via professional networks and social media platforms (WhatsApp, Telegram, and X). The survey instrument, adapted from validated international tools, was reviewed by experts and pilot-tested with 15 pharmacists (Cronbach’s alpha = 0.81). Data were analyzed using SPSS v26. Chi-square tests and t-tests were used to examine relationships between readiness and demographic/professional factors. Significance was set at p < 0.05.ResultsPharmacists exhibited moderate knowledge (mean = 13.8/20) and positive attitudes but reported training gaps and regulatory barriers. Most respondents supported early integration of palliative care, yet only 21.7% achieved full knowledge scores. Readiness was significantly higher among female (χ2 = 6.12, p = 0.047) and urban pharmacists (χ2 = 8.76, p = 0.013), while emotional preparedness and communication comfort remained comparatively low.ConclusionCommunity pharmacists in the Aseer region show strong willingness but limited preparedness for palliative care services. Addressing training deficiencies through structured modules and continuing education is essential. Developing national guidelines and targeted support programs will strengthen pharmacists’ roles and align their contributions with Vision 2030 healthcare goals.